2022
DOI: 10.3390/cancers14174195
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Angiogenesis-Related Long Non-Coding RNA and Identification of a Six-DEARlncRNA Signature Associated with Prognosis and Therapeutic Response in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a lethal gastrointestinal malignancy worldwide. We aimed to identify an angiogenesis-related lncRNAs (ARlncRNAs) signature that could predict the prognosis in ESCC. The GSE53624 and GSE53622 datasets were derived from the GEO database. The differently expressed ARlncRNAs (DEARlncRNAs) were retrieved by the weighted gene co-expression network analysis (WGCNA), differential expression analysis, and correlation analysis. Optimal lncRNA biomarkers were screened from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A ROC curve analysis showed that the AUCs for 6-DElncRNAs for predicting 1-, 3-and 5-year survival rates of patients with ESCC are 0.768, 0.825 and 0.822, respectively. As the high-risk group has higher gefitinib and lapatinib IC 50 values, 6-DElncRNAs may also be able to predict drug susceptibility (148). Liu et al (149) demonstrated that a 6-lncRNA signature (AC005091.1, SNHG6, AC091544.4, DNAJB5-DT, HTT-AS and ANKRD10-IT1) has a high predictive value for ESCC.…”
Section: Ncrnas As Biomarkers In Esccmentioning
confidence: 99%
“…A ROC curve analysis showed that the AUCs for 6-DElncRNAs for predicting 1-, 3-and 5-year survival rates of patients with ESCC are 0.768, 0.825 and 0.822, respectively. As the high-risk group has higher gefitinib and lapatinib IC 50 values, 6-DElncRNAs may also be able to predict drug susceptibility (148). Liu et al (149) demonstrated that a 6-lncRNA signature (AC005091.1, SNHG6, AC091544.4, DNAJB5-DT, HTT-AS and ANKRD10-IT1) has a high predictive value for ESCC.…”
Section: Ncrnas As Biomarkers In Esccmentioning
confidence: 99%
“…Currently, transcriptomics and chip analysis have found widespread application in various diseases [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%